NAVIGATING VIOLENCE AND GENDER EQUALITY IN CONTEMPORARY NIGERIAN POLITICAL CONTEXT - ADIGUN, IBIRONKE B. DOMINION; FATAI LATEEF YUSUF (International Studies Journal)
Violence and gender equality continue to be pressing concerns in contemporary Nigerian politics, posing significant challenges to the democratic process and the inclusion of marginalized groups, particularly women. In Nigeria, political campaigns and elections are often marred by violence, intimidation, and corruption, eroding the credibility of the democratic process and hindering the full participation of citizens. Women, in particular, face unique challenges in navigating the political landscape, with gender-based violence and discrimination creating barriers to their political participation and leadership. The patriarchal power structures that dominate Nigerian politics further marginalize women, making it difficult for them to access political positions and contribute effectively to decision-making processes. Efforts to address these challenges have been made, including the passage of laws and policies aimed at promoting gender equality and increasing women's representation in politics. However, implementation and enforcement remain major obstacles, as entrenched cultural norms and lack of political will limit the effectiveness of these measures. Additionally, the intersectionality of violence and gender equality with other social issues, such as poverty and lack of access to education, exacerbates the challenges faced by women in Nigerian politics.  This study provides a detailed analysis of the issues of violence and gender equality in Nigerian politics in the 21st century, through a historical analysis, this paper will explore the root causes, manifestations, and potential solutions to address these challenges.